Análise das publicações de influenciador digital fitness masculino no Instagram - Freire, Vanessa Regina Fernandes (Universidade Federal de São Carlos, 2024)
The research analyzed the publications posted by a digital fitness influencer on his Instagram, aggregating a corpus of comments from his followers. The objective was to identify the food proposals displayed by the influencer, also seeking to analyze what the influencer's followers were talking about through interactions in their publications. The theme will make it possible to verify how eating is perceived and exercised, discussing the consequences of this exposure to its followers, in the context of the representation of male body image exposed in society, as well as its social markers. This is a qualitative study of an exploratory nature, which observed the influencer's Instagram page, from January to April 2023, using Content Analysis (Bardin, 2016). The research highlighted the importance given to the influencer's publications as well as the followers' adoration for the content creator.
Analysis of male fitness digital influencer posts on Instagram
Keywords: Instagram; Influenciadores Digitais; Comportamento Alimentar; Cultura Fitness; Instagram; Fitness Culture; Eating Behavior; Digital Influencers; CIENCIAS HUMANAS